Metabolism of Carotenoids and β-Ionone Are Mediated by Carotenogenic Genes and PpCCD4 Under Ultraviolet B Irradiation and During Fruit Ripening - Liu, Hongru; Cao, Xiangmei; Azam, Muhammad; Wang, Chunfang; Liu, Chenxia; Qiao, Yongjin; Zhang, Bo (Frontiers in Plant Science, 2022)
Carotenoids are essential pigments widely distributed in tissues and organs of higher plants, contributing to color, photosynthesis, photoprotection, nutrition and flavor in plants. White- or yellow-fleshed colors in peach were determined by expression of carotenoids cleavage dioxygenase (PpCCD) genes, catalyzing degradation of carotenoids. The cracked volatile apocarotenoids are main contributors to peach aroma and flavor with low sensory threshold concentration. However, the detailed regulatory roles of carotenoids metabolism genes remained unclear under UV-B irradiation. In our study, metabolic balance between carotenoids and apocarotenoids were regulated by expression of phytoene synthase (PSY), β-cyclase (LCY-B), ε-cyclase (LCY-E) and PpCCD4 under UV-B irradiation. Transcript levels of PpPSY, PpLCY-B, PpLCY-E, PpCHY-B elevated 2-10-fold compared with control, corresponding to nearly 30% increase of carotenoids content after 6 h UV-B irradiation. Interestingly, total carotenoids content reduced nearly 60% after 48 h storage, while UV-B delayed decline of lutein and β-carotene. Transcript level of PpLCY-E increased 17.83-fold compared to control, partially slowing the decline rate of lutein under UV-B irradiation. In addition, transcript level of PpCCD4 decreased to 30% of control after 48 h UV-B irradiation, in accord with dramatically reduction of apocarotenoid volatiles and the delayed decrease of β-carotene. Besides, β-ionone content was elevated by ethylene treatment, and accumulation dramatically accelerated at full ripen. Taken together, UV-B radiation mediated the metabolic balance of carotenoid biosynthesis and catabolism by controlling transcript level of PpPSY, PpLCY-B, PpLCY-E, PpCCD4 in peach, and transcript level of PpCCD4 showed positive relationship with accumulation of β-ionone during ripening process. However, the detailed catalytic activity of PpCCD4 with various carotenoid substrates need to be studied further, and the key transcript factors involved in the regulation of metabolism between carotenoids and apocarotenoids need to clarify.